(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role, importance and practical activities of the Institute of Scientific and Legal Expertise in improving the quality of regulatory and legal documents. It also analyzes the legal basis of the Institute of Expertise, as well as its functions in eliminating conflicts, duplicate norms and legal gaps that arise in draft regulatory and legal documents.